Effectiveness of music interventions for patients undergoing needle biopsy: A systematic review and meta-analysis - Wenrui Han; Min Zhang; Min Luo; Quanxing Su; Yahui Guan (Complementary Therapies in Medicine)
Introduction: Percutaneous biopsy is a routine diagnostic procedure often associated with anxiety and pain. Music intervention, a simple and low-cost non-pharmacological approach, has been widely used to reduce psychological distress in clinical settings. This study evaluates its effectiveness in patients undergoing biopsy. Methods: A comprehensive systematic search was conducted across multiple databases, including PubMed, Embase, the Cochrane Library, Web of Science, MEDLINE, ProQuest, CINAHL, and major Chinese databases (CBM, CNKI, VIP, and Wanfang), from the inception of each database to November 20, 2024. Eligible studies assessing the effects of music interventions on anxiety and pain during biopsy procedures were identified. Two independent reviewers screened titles, abstracts, and full texts, extracted relevant data, and resolved discrepancies through discussion or consultation with a third reviewer. Meta-analysis was conducted using RevMan 5.4.1 and Stata 16.0. Result: A total of 16 studies met the inclusion criteria. Pooled analysis revealed that music interventions significantly reduced both anxiety and pain in patients undergoing biopsy. The anxiolytic effect was particularly significant in prostate biopsy procedures and consistent across various age groups. Regarding pain management, music interventions demonstrated overall efficacy, with especially pronounced effects observed during bone marrow and prostate biopsies. Subgroup analyses indicated pain relief across different age groups. Conclusion: Music intervention is an effective, non-invasive, and drug-free approach to alleviate anxiety and pain associated with biopsy procedures, particularly those that are more invasive. While current findings are promising, further large-scale, high-quality randomized controlled trials are warranted to strengthen the evidence base and inform clinical guidelines.